Faktor Social Support Colleagues Paling Berpengaruh Terhadap Job Performance Karyawan Perbankan - Siti Lolita Sari; Dita Oki Berliyanti; Wiwik Robiatul Adawiyah (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to analyze the effect of Job Involment, Social support colleagues, Job related anxiety on Job Performance. Job Involment is a normative belief about the value of work in the life of an incumbent and this state of attitude is the result of previous cultural and socialization activities. Social support from colleagues can include instrumental assistance to complete work tasks, it can also be a type of emotional support to prevent the health consequences of stressful work experiences. Job related anxiety describes the tension that employees experience in carrying out their work duties because employees worry about organizational functions and their ability to meet superiors' expectations. Job Performance is As a behavioral skill that employees use to perform various aspects of their job. a role that directly or indirectly contributes to the goals of the company. This type of research is a quantitative method. The sampling method used is convenience sampling with 245 employees of PT Bank Mandiri Tbk (Persero) in the big rice fields of central Jakarta. Data analysis techniques in this study used instrument testing techniques with validity and reliability. Validity relates to the accuracy of the instrument in measuring the variables to be studied, while reliability relates to the consistency, accuracy, and predictability of a measuring instrument. and there is a hypothesis test carried out using the multiple linear regression method with the SPSS version 21 program. Hypothesis testing is carried out by comparing the p-value or level of significance (alpha) of 0.05. The results of this study indicate that Job Involment, Social support colleagues, Job related anxiety have a positive effect on Job Performance. The managerial implication in this research is that it is expected that leaders in organizations implement social support colleagues, so that employees become more comfortabel at work. The company is expected to be able to foster good relationships with employees so that Job related anxiety employees feel that their work has become a definite responsibility. Good relationships from superiors and subordinates will create effective work so Job Involvement is very important for workers.